Changing the policy paradigm: A benefit maximization approach to electricity planning in developing countries. (15th April 2020) - Nock, Destenie; Levin, Todd; Baker, Erin
Highlights: Integrated stakeholder preferences towards equality into electricity planning. Framework for opportunity-focused approach for electricity planning. Novel combination of economics, utility maximization, and least-cost frameworks. Co-optimized generation and transmission investments under equality preferences. Abstract: Access to electricity can lead to enhanced education, business, and healthcare opportunities. Governments in emerging economies are often faced with the challenge of increasing access to electricity and reducing system inequality, while operating under severe budget constraints. This paper develops a methodology for finding the optimal expansion of a power system under the objective of maximizing social benefit, as it relates to distributional equality for electricity access, subject to a budget constraint. This contrasts with traditional models, which minimize the cost of satisfying projected electricity demand. We formulate a generation expansion planning problem as a utility-maximization mixed-integer linear program and apply it to a case study analysis of a low-income country with limited electricity infrastructure. We focus our analysis on understanding how the optimal allocation of generation between centralized and distributed resources is impacted by stakeholder preferences toward equality and different budget levels. We find that a high preference for equality leads to lower overall electricity consumption levels, but improved electrification rates due to greater investment (300–750 km increase) in transmission infrastructure. If stakeholders move from a low to a high equality preference then they could see a 72–87% increase in energy access equality rating depending on the budget. Conversely, indifference to equality leads to higher overall consumption levels in urban areas but reduced electrification rates. This methodology can help decision makers evaluate the social trade-offs between improving energy access, reducing energy inequality and poverty, and increasing total electricity consumption when operating under budget constraints in their countries.